Perubahan Sosial di Kelurahan Tello Baru Melalui Program Lorong Wisata - Asrianto; Muhammad, Rahmat; Raf, Nuvida (Universitas Muhammadiyah Sorong, 2023)
Social changes that occur in Tello Baru Village into ecotourism are not only environmental changes but also social and economic changes. These changes are changes planned by agents and structures. This study aims to analyze the relationship between agents and structures in creating social change in Tello Baru Village into ecotourism through the Lorong Wisata program. The research analysis uses Anthony Giddens' structuration theory which explains the relationship between agents and structures. The research used qualitative methods using observation, interview and documentation data. The research findings show that the relationship between agents and structures is established through social practices of domination, significance and legitimacy. The domination owned by the agent is control over society and facilities. The social practice of the significance cluster is realized through the production of discourse by the agent's mastery in ecotourism management. The legitimacy cluster is realized when the agent gets structural support from the Makassar City government.